Mathematical Cognition and Understanding Perspectives on Mathematical Minds in the Elementary and Middle School Years - Robinson, Katherine M.; Dubé, Adam K.; Kotsopoulos, Donna (Springer International Publishing : Imprint: Springer, 2023)
X, 287 p. 1 illus.